Pemanfaatan Classroom Dan Zoom Saat Darurat Kabut Asap Berdasarkan Perspektif Mahasiswa IAN Universitas Palangka Raya - Kurnia Senantiasa Zai; Misnawati Misnawati; Yesni Nopy; Ervawaty Ervawaty; Ardianto Ardianto (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The purpose of this study was to determine the perspective of State Administration students on the utilization of Classroom and Zoom Meeting during the Haze Emergency Response Status. This research uses a qualitative descriptive method that aims to describe the analysis of the results of questionnaires, interviews, and literature studies. The subjects and objects in this study were students of Palangkara Raya University as many as 98 respondents in the first and third semester who were taking the State Administration Study Program. Data collection techniques were carried out by distributing online questionnaires, interviews, and literature studies. The results showed that the use of Classroom and Zoom Meeting applications provided convenience in online learning activities (38.9% Agree), the use of Classroom and Zoom Meeting applications in learning became more flexible (68.4% Agree), online learning through Classroom and Zoom Meeting applications became more complicated (15% Agree), online learning on campus by utilizing Classroom and Zoom Meeting applications made it easy to collaborate between students (50% agree), The use of Google Classroom and Zoom Meeting applications gives students confidence in expressing opinions and asking questions (35% Agree), Classroom and Zoom Meeting applications are very relevant to use for distance learning between students and lecturers (40.9%), Lecturers respond to questions and opinions when learning using classrooms and Zoom Meeting (54.5% agree). It can be concluded that the utilization of Google Classroom and Zoom Meeting during the Haze Emergency Response Status received a good perception from students and lecturers are advised to always motivate students to take part in online learning as long as the Haze is still there.